Research on the expected utility of the nudge-based intervention strategy for healthy eating behavior in online catering - Dai, Xiaoting; Wu, Linhai (Frontiers in Public Health, 2025)
IntroductionWhile the rise of the new consumption format of “Internet + Food” has changed the global food environment, it has also caused people to worry about the health risks brought about by the unreasonable dietary structure of online catering foods. Under the online catering consumption model based on electronic transactions, compared with traditional tough intervention policies, the nudging strategy can make full use of the advantages of information technology and effectively promote consumers’ choice of healthy diet to interfere with the dietary behavior of online catering consumers.MethodsThe objective of this study is to design a choice environment on online platforms through nudge strategies, so as to reduce the cognitive resistance and inertia of consumers in decision-making. By means of guidance rather than coercion, it enables consumers to make healthy choices more easily and proactively, thereby promoting the occurrence of healthy eating behaviors invisibly. Based on the subdividing of respondents based on the characteristics of consumer groups, we explored the different expected intervention effects of providing decision information, changing decision structure, and providing decision-making assistance-type nudging strategies on consumers with different characteristics. This paper divides the nudging strategies into three categories: providing decision information type, changing decision structure type, and providing decision assistance type. The subjects of this paper must be consumers who have their own experience of eating online food and beverages. A total of 44,050 valid samples were collected.ResultsThe results found that nudging strategies have a positive impact on healthy eating behaviors; specifically, women, lower education, lower income consumers, and chronic patients are more susceptible to the healthy diet-nudging strategies.DiscussionCompared with providing decision-making information type and changing decision-making structure type by constructing multinomial logistic regression models, the intervention effect of providing decision-making auxiliary nudging strategies is slightly insufficient. Changing the structural nudge strategy of decision-making is more influential among high-age, low-education and low-income consumer groups.